Efektivitas Waktu Aplikasi PBZ terhadap Pertumbuhan Vegetatif Tanaman Padi dengan Sistem Integrasi Padi – Kelapa Sawit - Bambang Surya Adji Syahputra; Ruth Riah Ate Tarigan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The main problem in ricefields on North Sumatra has been changing function of this area to oil palm plantations which continuities every year, on the other hand, we need foods are increase with following the increase of population from year to year. Although the North Sumatra food data’s shown that it has been fulfilling in self-sufficiency food, instead of rice production surplus for the region, but the program to increase production must be continuously, in order to survive with the surplus or more increase for the future. Some of efforts are, like using marginal land, planting rice under oil palm plants and rubber as well as using the house roof to planting the rice. This research was used a Split Plot Design (RPT) with 5 replications. As Main Plots (PU) are rice varieties (Inpari Sidenuk and Mekongga) and Sub Plots (AP), namely application time (one week before IM, during IM and one week after IM). PBZ was applied at concentration 400 ppm evenly distributed to plants. Fertilizers were used N (urea), P (TSP) and K (KCl) with government recommended doses, where P and K fertilizers were applied as basic fertilizer while N was applied at 3 times. Control of pests, diseases and weeds were carried out according to basic standards, namely using pesticides if the attack has exceeded the economic threshold. Vegetative growth was measured; plant height, stem diameter and flag leaf area. For plant height before application PBZ was given the same results (not significantly different) but after application, the best time was founded a week before IM. Likewise the measurement results for the diameter of the stem was given significantly different results among the time of application before IM compared to IM and after IM. Unlike results with the parameters of flag leaf area, which was the highest number founded in the application after IM and significantly different compared before IM and at IM, respectively. Interactions between varieties and time application of PBZ did not given significantly different. The conclution that the PBZ application before IM was given good and significantly results as compared to after and during IM, respectively.